ORAI channels are critical for receptor-mediated endocytosis of albumin - Bo Zeng (Nature Portfolio, 2017)
Patients with diabetic nephropathy suffer from impaired albumin reabsorption by proximal tubular epithelial cells. Here authors use diabetic and transgenic mouse models and in vitro models to show the cause for this lies in the down regulation and internalization of the ion channels, ORAI1-3.